KEPENTINGAN INDONESIA MENYEPAKATI KERJASAMA EKONOMI DENGAN SLOVAKIA DALAM BIDANG ENERGI DAN INFRASTRUKTUR - Agita Suryadi; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes the interest of Indonesia to agreed about the economic cooperation with Slovakia in energy and infrastructure. As a development state Indonesia need a increase of energy and infrastructure supply to keep a energ supplied. In order Slovakia are a state in europe and have a potencial resources in energy supply.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze interest of Indonesia to agreed about the economic cooperation with Slovakia in energy and infrastructure. The theories applied in this research are liberalisme perspective, nation state analyze and international ccoperation theory.The research shows that interest of Indonesia to agreed about the economic cooperation with Slovakia in energy and infrastructure are to increase a income of Indonesia from energy and infrastructure capital. This agreement have done in 2009 until 2012, with the built of volt resources in some place in Indonesia like Batam Island and built semen company.Key words: cooperation, interest, energy, infrastructure.